The apoptotic actions of platelets in acute ischemic stroke - ŞENER, AZİZE (SPRINGER, 2013)
Stroke is a disease that affects the blood vessels that supply blood to the brain. Although platelets are implicated in the pathophysiology of stroke the mechanism is still not clear and there antiplatelet agents available for the prevention and treatment of stroke. We herein examined the relationship between the potential cytokine, TNF-alpha platelet activation and apoptosis in acute ischemic stroke patients. We selected 60 patients (mean age 57.9 +/- A 10.2 years) who had not taken any antiplatelet drugs for 14 days. A group of 45 participants (mean age 51.05 +/- A 9.07 years) were selected as the control group. For both the patients and for the control group, P-selectin (CD62p) and Annexin-V binding, cytochrome-c levels, caspase-3 gene expression and caspase-3 releasing and plasma TNF-alpha levels were measured in platelets. The results showed significant increase in plasma TNF-alpha and platelet Annexin-V, CD62p, cytochrome-c and caspase-3 gene expression in stroke patients compared to the control group. The data of this work suggests that inflammation may have a role in platelet apoptosis in stroke which may suggest a new aspect of the role of inflammation in the development of acute ischemic stroke.
Keywords: Apoptosis; Caspase-3; Stroke; Platelets; Inflammation; TUMOR-NECROSIS-FACTOR; MITOCHONDRIAL PERMEABILITY TRANSITION; ANNEXIN-V BINDING; FACTOR-ALPHA; TNF-ALPHA; FLOW-CYTOMETRY; P-SELECTIN; ACTIVATION; ADHESION; INFLAMMATION